Combined Testing Standard Analysis of Electric Drive System for Rail Transit Vehicle - LIAO Chang-xin; LIU Gui (机车电传动)
According to matching characteristic of electric drive system combined testing for rail transit vehicle applied to validate characteristic matching of motor(s), inverter and their control system, combined testing standard IEC 61377 was introduced. Testing project operation and new development of the standard were discussed.